Програмна система для астматиків «noasthma» - Іваненко, В. Ю. (ХНУРЕ, 2020)
Asthma is a chronic respiratory disease. According to WHO, in 2019, 235 million people worldwide suffer from asthma, and their numbers are on the rise. In Ukraine, bronchial asthma officially covers less than 1% of the population, but we do not know how many Ukrainians suffer from this disease without a diagnosis. In medical practice, bronchial asthma is recognized as an incurable disease, but its symptoms, fortunately, can be controlled. Modern mobile technologies are able to facilitate the daily routine of patients. With the help of special applications, asthmatics can control their condition and monitor their well-being. And one of them is the NoAsthma app